PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP MINAT NASABAH DALAM MENGGUNAKAN PRODUK TABUNGAN HAJI INDONESIA: (Studi Nasabah Bank Syariah Indonesia KCP Mojokerto Mojopahit 2) - Nurul Azizah Ria Kusrini; Kafi Masturo (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Various promotional steps have been taken by BSI KCP Mojokerto Mojopahit 2 in introducing Hajj savings products to the public. However, the results are still not as expected. For this reason, this study was conducted to determine whether promotion and product quality affect customer interest in using Indonesian Hajj savings products. This study uses a quantitative method using a questionnaire as a data instrument. Respondents from this questionnaire were 65 respondents. The collected data was processed using SPSS 28. The results of this study indicate that promotion has a significant effect on customer interest with a value of tcount (2,932) > ttable (1,998) and a significance value of 0,005 < 0,05. 2). Product quality has a significant effect on customer interest with tcount (2.913) > ttable (1.998) and a significance value of 0.005 <0.05. 3). Promotion and Product Quality have a significant effect on customer interest with the results of the f (simultaneous) test showing that the significance value is 0.003 <0.05 and the fcount is 6.464 > ttable 3.15.